Bias Politik Pesantren: Dari Pragmatisme Transaksional Hingga Resistensi Sosial - ERNAS, SAIDIN (Jurnal Studi Pemerintahan, 2011)
Nowadays more and more out of boarding school as a primary function of Islamic educationalinstitutions and engage in practical politics. An action that causes a variety of social and politicalimplications that ought to be observed scientifically. This paper describes an important finding thatsuccessful boarding school involvement in politics, despite the economic added-value material thatbenefit schools, but it has grown factual in-transactional pragmatic political behavior and at the sametime reduce the legitimacy of public schools and cause resistance to the political attitudes of pesantren